Erratum (Academy of Management Journal, 2005)
The article presents a correction to the article “Human Resource Management and Labor Productivity: Does Industry Matter',” by Deepak K. Datta, James P. Guthrie, and Patrick M. Wright, published in the February 2005 issue of the “Academy of Management Journal.”